A Novel Gemcitabine-Resistant Gallbladder Cancer Model Provides Insights into Molecular Changes Occurring during Acquired Resistance - Vergara-Gomez, Luis; Bizama, Carolina; Zhong, Jun; Buchegger, Kurt; Suarez, Felipe; Rosa, Lorena; Ili, Carmen; Weber, Helga; Obreque, Javiera; Espinoza, Karena; Repetto, Gabriela; Roa, Juan C.; et al. (My University, 2023)
Treatment options for advanced gallbladder cancer (GBC) are scarce and usually rely on cytotoxic chemotherapy, but the effectiveness of any regimen is limited and recurrence rates are high. Here, we investigated the molecular mechanisms of acquired resistance in GBC through the development and characterization of two gemcitabine-resistant GBC cell sublines (NOZ GemR and TGBC1 GemR). Morphological changes, cross-resistance, and migratory/invasive capabilities were evaluated. Then, microarray-based transcriptome profiling and quantitative SILAC-based phosphotyrosine proteomic analyses were performed to identify biological processes and signaling pathways dysregulated in gemcitabine-resistant GBC cells. The transcriptome profiling of parental and gemcitabine-resistant cells revealed the dysregulation of protein-coding genes that promote the enrichment of biological processes such as epithelial-to-mesenchymal transition and drug metabolism. On the other hand, the phosphoproteomics analysis of NOZ GemR identified aberrantly dysregulated signaling pathways in resistant cells as well as active kinases, such as ABL1, PDGFRA, and LYN, which could be novel therapeutic targets in GBC. Accordingly, NOZ GemR showed increased sensitivity toward the multikinase inhibitor dasatinib compared to parental cells. Our study describes transcriptome changes and altered signaling pathways occurring in gemcitabine-resistant GBC cells, which greatly expands our understanding of the underlying mechanisms of acquired drug resistance in GBC.
Keywords: gallbladder cancer; acquired drug resistance; gemcitabine; epithelial-to-mesenchymal transition; gene expression profiling; silac-based phosphoproteomics; cytidine deaminase